Disney's Atlantis Milo's return - Hart, Thomas; Stones, Tad; Shelton, Toby; Cook, Victor A. (Walt Disney Home Entertainment distributed in the Philippines by Viva Video, 2003)
Milo, Kida and their team gear up for more action when trouble surfaces above water, threatening the famous and mysterious underwater kingdom of Atlantis. They discover that mystifying powers are at work.